2014
DOI: 10.1371/journal.pone.0094090
|View full text |Cite
|
Sign up to set email alerts
|

Low Dose Influenza Virus Challenge in the Ferret Leads to Increased Virus Shedding and Greater Sensitivity to Oseltamivir

Abstract: Ferrets are widely used to study human influenza virus infection. Their airway physiology and cell receptor distribution makes them ideal for the analysis of pathogenesis and virus transmission, and for testing the efficacy of anti-influenza interventions and vaccines. The 2009 pandemic influenza virus (H1N1pdm09) induces mild to moderate respiratory disease in infected ferrets, following inoculation with 106 plaque-forming units (pfu) of virus. We have demonstrated that reducing the challenge dose to 102 pfu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
54
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 29 publications
7
54
0
Order By: Relevance
“…Evaluation of different doses for viral inoculation has been described for mice, ferrets, and occasionally in humans, but not yet for nonhuman primates (5)(6)(7)(8)(9)(10)(17)(18)(19)(20)(21). These studies were either directed at finding the minimal infectious dose or minimal lethal dose or, in case of evaluation of attenuated viruses in humans, at finding the dose that resulted in adequate levels of infection while limiting development of clinical symptoms and fever.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evaluation of different doses for viral inoculation has been described for mice, ferrets, and occasionally in humans, but not yet for nonhuman primates (5)(6)(7)(8)(9)(10)(17)(18)(19)(20)(21). These studies were either directed at finding the minimal infectious dose or minimal lethal dose or, in case of evaluation of attenuated viruses in humans, at finding the dose that resulted in adequate levels of infection while limiting development of clinical symptoms and fever.…”
Section: Discussionmentioning
confidence: 99%
“…A relation between inoculation dose and virus replication in nasal washes has been reported in several human studies (17,18,21), but other studies have shown no relation (19,20). Also, in ferrets conflicting results on the relation between virus inoculation dose and levels of virus replication have been reported (6,(8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this dose is unrealistically high compared with typical infectious doses in humans, which have been shown to be as low as 3 TCID 50 following exposure to small-particle influenza virus aerosols (34,35). Similarly, studies quantitating the 50% infectious dose of influenza viruses in the ferret (FID 50 ) have revealed that both avian and human influenza viruses are capable of high infectivity in this species, with doses under 10 PFU leading to productive ferret infection following inhalation of virus-containing aerosols (24,36). Low-dose infection has also been documented following inoculation of ferrets by the ocular route (28).…”
Section: Inoculation Dosementioning
confidence: 99%
“…Ferrets are the preferred animal model to assess influenza virus infection, virulence and transmission (Govorkova et al, 2007;Itoh et al, 2009;Maines et al, 2009;Munster et al, 2009;Zhang et al, 2013), and have been widely used in antiviral studies to assess drug effectiveness (Govorkova et al, 2007(Govorkova et al, , 2011Marriott et al, 2014;Oh et al, 2015), different treatment strategies (Maines et al, 2009;Oh et al, 2014) and the selection of resistant viruses (Hurt et al, 2010). Because oseltamivir, the most widely used NAI globally, is an orally administered drug, delivery to ferrets (or other animals) is relatively straightforward.…”
Section: Introductionmentioning
confidence: 99%